A Mur regulator protein in the extremophilic bacterium Deinococcus radiodurans. - Amir Miraj Ul Hussain Shah (Public Library of Science (PLoS), 2014)
Ferric uptake regulator (Fur) is a transcriptional regulator that controls the expression of genes involved in the uptake of iron and manganese, as well as vital nutrients, and is essential for intracellular redox cycling. We identified a unique Fur homolog (DR0865) from Deinococcus radiodurans, which is known for its extreme resistance to radiation and oxidants. A dr0865 mutant (Mt-0865) showed a higher sensitivity to manganese stress, hydrogen peroxide, gamma irradiation and ultraviolet (UV) irradiation than the wild-type R1 strain. Cellular manganese (Mn) ion (Mn2+) analysis showed that Mn2+, copper (Cu2+), and ferric (Fe3+) ions accumulated significantly in the mutant, which suggests that the dr0865 gene is not only involved in the regulation of Mn2+ homeostasis, but also affects the uptake of other ions. In addition, transcriptome profiles under MnCl2 stress showed that the expression of many genes involved in Mn metabolism was significantly different in the wild-type R1 and DR0865 mutant (Mt-0865). Furthermore, we found that the dr0865 gene serves as a positive regulator of the manganese efflux pump gene mntE (dr1236), and as a negative regulator of Mn ABC transporter genes, such as dr2283, dr2284 and dr2523. Therefore, it plays an important role in maintaining the homoeostasis of intracellular Mn (II), and also other Mn2+, zinc (Zn2+) and Cu2+ ions. Based on its role in manganese homeostasis, DR0865 likely belongs to the Mur sub-family of Fur homolog.